Diagnosis of Rosai-Dorfman Disease in Elderly Female on Fine Needle Aspiration Cytology: A Case Report - Meher Aziz; Prasenjit Sen Ray; Nazima Haider; Sumit Prakash Rathore (Hindawi Limited, 2012)
Rosai-Dorfman disease (RDD) is a rare benign disorder of histiocytic proliferation that usually presents with bilateral cervical lymphadenopathy in children. We describe the case of a 50-year-old lady suffering from this disease who presented with generalized lymphadenopathy and a left sided chest wall lump. Fine needle aspiration cytology (FNAC) from all the lesions showed abundant benign histiocytes with lymphophagocytosis which was compatible with the diagnosis of RDD. This case is being reported for its rarity in presentation in an elderly female with both generalized nodal as well as extranodal manifestations.